Portal Vein Thrombosis: Diagnosis and Endovascular Management - Ju, Connie; Li, Xin; Gadani, Sameer; Kapoor, Baljendra; Partovi, Sasan (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Background Portal vein thrombosis (PVT) is a rare but severe entity that can cause clinically significant sequela such as worsening portal hypertension or mesenteric ischemia. Those cases refractory to medical management may be referred for endovascular intervention. Several technical considerations have been described in the literature, but a cohesive comparison of these multiple techniques is lacking.Methods The purpose of this article is to review the diagnosis and endovascular management of PVT, including areas in which further research is warranted.Results Cases of PVT can be readily diagnosed using ultrasound, computed tomography, or magnetic resonance imaging. Treatment often begins with systemic anticoagulation and endovascular interventions may be used in selected cases. Determining the optimal approach to accessing the portal venous system depends on the underlying disease and chronicity of the thrombus and the degree of occlusion. Once access to the portal venous system is established, catheter-directed therapy may be performed to achieve recanalization.Conclusion Despite the heterogeneity in patient presentation, cases of PVT can be readily diagnosed across several imaging modalities. Strategizing interventional approaches involves evaluation of the underlying disease and the chronicity of the thrombus.Key Points: Citation Format
Keywords: portal vein thrombosis; thrombolysis; TIPS; interventional procedures